2019
DOI: 10.3390/ijms20030499
|View full text |Cite
|
Sign up to set email alerts
|

Unacylated Ghrelin Improves Vascular Dysfunction and Attenuates Atherosclerosis during High-Fat Diet Consumption in Rodents

Abstract: Unacylated ghrelin (UnGhr) exerts several beneficial actions on vascular function. The aim of this study was to assess the effects of UnGhr on high-fat induced endothelial dysfunction and its underlying mechanisms. Thoracic aortas from transgenic mice, which were overexpressing UnGhr and being control fed either a standard control diet (CD) or a high-fat diet (HFD) for 16 weeks, were harvested and used for the assessment of vascular reactivity, endothelial nitric oxide synthase (eNOS) expression and activity, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 53 publications
0
23
0
Order By: Relevance
“…The resulting peptide analogue, [Dpr 3 (octanoyl), Lys 19 (triazole-ADIBO-F)]ghrelin(1-19) (13), was found to have an IC 50 value of 9.7 nM and was labeled with fluoride-18 to produce [ 18 F]13 in radiochemical yields of 64-66% and molar activities of 0.6-0.9 GBq/mmol. 82 Charron et al continued with this theme and reported a probe containing a 1,4,7,10-tetraazacyclododecane-1,4,7,10tetraacetic acid (DOTA) chelator off the C-terminal lysine residue (Figure 8), [Dpr 3 (octanoyl), Lys 19 (Ga-DOTA)]ghrelin (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) (14), which possessed an IC 50 value of 5.9 nM, comparable to natural ghrelin (IC 50 ¼ 3.1 nM). 58 The probe was labeled with gallium-68 in radiochemical yields of 54%-83% and molar activities of 10.2-22.8 GBq/mmol.…”
Section: Molecular Imaging Agents Based On Ghrelinmentioning
confidence: 99%
See 4 more Smart Citations
“…The resulting peptide analogue, [Dpr 3 (octanoyl), Lys 19 (triazole-ADIBO-F)]ghrelin(1-19) (13), was found to have an IC 50 value of 9.7 nM and was labeled with fluoride-18 to produce [ 18 F]13 in radiochemical yields of 64-66% and molar activities of 0.6-0.9 GBq/mmol. 82 Charron et al continued with this theme and reported a probe containing a 1,4,7,10-tetraazacyclododecane-1,4,7,10tetraacetic acid (DOTA) chelator off the C-terminal lysine residue (Figure 8), [Dpr 3 (octanoyl), Lys 19 (Ga-DOTA)]ghrelin (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) (14), which possessed an IC 50 value of 5.9 nM, comparable to natural ghrelin (IC 50 ¼ 3.1 nM). 58 The probe was labeled with gallium-68 in radiochemical yields of 54%-83% and molar activities of 10.2-22.8 GBq/mmol.…”
Section: Molecular Imaging Agents Based On Ghrelinmentioning
confidence: 99%
“…However, DAG does participate in physiological pathways independent of the GHSR including binding to the corticotropin releasing factor receptor type 2a (CRF2a), exerting beneficial actions on vascular function, and cardiac protection. [17][18][19] Additionally, a cyclic analogue of DAG, known as Livoletide, is currently in phase III clinical trials for the treatment of Prader-Willi syndrome. 20 The GHSR-1b isoform does not bind ghrelin or growth hormone secretagogues and, therefore, does not share the same signaling profile as the GHSR-1a.…”
Section: The Ghsr and Its Endogenous Ligandsmentioning
confidence: 99%
See 3 more Smart Citations